PHYTOTOXICITY OF DIMETHYL SULFOXIDE IN THE GROWTH TEST - Tkachuk, Nataliia; Zelena, Liubov; Novikov, Yaroslav; Taranenko, Veronika (Biota. Human. Technology, 2024)
Dimethyl sulfoxide (DMSO) is widely used as an industrial solvent and for a variety of medical purposes. Reports of the toxicity of DMSO to living organisms vary. The plants Lepidium sativum L. and Raphanus raphanistrum subsp. sativus (L.) Domin. are widely used in the biotesting of toxicants. Currently, there is no information on the phytotoxicity of aqueous solutions of DMSO for these test plants, which determined the aim of this study. Methodology. Phytotoxicity of aqueous DMSO solutions was assessed using a growth test. The following plants were used as test plants: 1) seed radish (R. raphanistrum subsp. sativus) of the French breakfast variety, 10 seeds of which were placed in a Petri dish on filter paper moistened with distilled water (control) or 0.5 %, 1.0 %, 5.0 %, 10.0 %, 25.0 % or 45.0 % aqueous solution of DMSO (experiment); 2) watercress (L. sativum) of the Aphrodite variety, 10 seeds of which were placed in a Petri dish on filter paper moistened with distilled water (control) or a 0.025 %, 0.05 % or 0.1 % aqueous solution DMSO (experiment). The research was carried out in triplicate for 6 days (radish) and 5 days (watercress), during which the energy of seed germination of test plants (%) was determined on the 3rd day, on the 6th day (radish) and on the 5th day (watercress) – seed germination (%) and biometric and morphometric indicators of test plant seedlings (root and aerial part length, mm). Scientific novelty. In a growth test with R. raphanistrum subsp. sativus showed extreme phytotoxicity for 5.0-45.0 % aqueous DMSO solutions and no phytotoxicity for 0.025-1.0 % aqueous DMSO solutions in a growth test with L. sativum and R. raphanistrum subsp. sativus. Conclusions. Aqueous solutions of DMSO in concentrations of 0.025-1.0 % did not show phytotoxic properties according to the growth test with L. sativum and R. raphanistrum subsp. sativus, in contrast to 5.0-45.0 % solutions, which showed extreme phytotoxicity according to the growth test with R. raphanistrum subsp. sativus. The obtained results indicate that this substance will not inhibit plant growth at concentrations found in wastewater (0.05-0.08 %).